2011
DOI: 10.1088/0029-5515/51/7/073012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of plasma rotation effects on the stability of type-I edge-localized mode in tokamaks

Abstract: Mechanisms of plasma rotation effects on edge magnetohydrodynamic (MHD) stability are investigated numerically by introducing energies that are distinguished by physics. By comparing them, it is found that an edge-localized MHD mode is destabilized by the difference between the eigenmode frequency and the equilibrium toroidal rotation frequency, which is induced by rotation shear. In addition, this destabilizing effect is found to be effective in the shorter wavelength region. The effect of poloidal rotation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 21 publications
(36 reference statements)
2
50
0
Order By: Relevance
“…Analysis of ELM stability with extended MHD models in JET, JT-60U and future JT-60SA tokamak plasmas N Aiba 1 , S Pamela 2 , M Honda 3 , H Urano 3 , C Giroud 2 , E Delabie 4 , L Frassinetti 5 , I Lupelli 2 , N Hayashi 3 , G Huijsmans 6,7 , the JET Contributors 8 and JT-60SA Research Unit 9…”
Section: Plasma Physics and Controlled Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of ELM stability with extended MHD models in JET, JT-60U and future JT-60SA tokamak plasmas N Aiba 1 , S Pamela 2 , M Honda 3 , H Urano 3 , C Giroud 2 , E Delabie 4 , L Frassinetti 5 , I Lupelli 2 , N Hayashi 3 , G Huijsmans 6,7 , the JET Contributors 8 and JT-60SA Research Unit 9…”
Section: Plasma Physics and Controlled Fusionmentioning
confidence: 99%
“…Therefore, it is necessary to develop operation scenarios and/or control techniques in order to avoid such large ELM heat loads. The important presupposition required to achieve this objective is the precise prediction of the plasma conditions triggering the ELM, and many past works have shown that a stability analysis with the ideal MHD model has successfully explained the plasma conditions observed in the experiments [1][2][3]. These results proved that the type-I ELM is triggered by an ideal MHD mode, called a peelingballooning mode (PBM), and the trigger condition is determined by the amount of plasma pressure and current density near the edge transport barrier region (pedestal).…”
Section: Introductionmentioning
confidence: 99%
“…33,36 The effect on the stability of peeling modes is negligible. 36 In JT60U, analysis of the pedestal stability 37 showed that the pedestal is well below the MHD stability limit when the (counter) toroidal rotation was neglected. In this case, the counter toroidal rotation was found to have a significant destabilising effect on the most unstable modes.…”
Section: A Linear Mhd Stability Limitsmentioning
confidence: 99%
“…If the electrostatic potential is a flux function, equations (5), (6) and (7) can be simply combined to obtain a variant of equation (16) accounting for arbitrary poloidal density variations. This would be the case if the impurity concentration is small and the inertial effects are negligible for the main ions.…”
Section: Theoretical Background and Measurement Principlementioning
confidence: 99%